AN ANALYSIS OF FLOUTING MAXIM IN ANYONE BUT YOU (2023) FILM - Diva Laili Ardelia; Nita Maya Valiantien (Fakultas Ilmu Budaya Universitas Mulawarman, 2026)
Communication plays a crucial role in daily interactions, and to ensure effective exchanges, certain conversational rules must be followed. When these rules are intentionally broken, the resulting implications often reveal more than the words themselves. This research analyzes the flouting of conversational maxims as proposed by Grice in the romantic comedy film Anyone But You (2023), focusing on the main characters, Bea and Ben. Using a qualitative descriptive method, the study identifies and categorizes instances in which the characters flout the maxims of quantity, quality, relation, and manner, and aims to identify the strategies they use to flout these maxims. The data, drawn from the characters' dialogues, reveal how flouting is employed to express emotional complexity, especially in the context of their love-hate relationship. The results show that Bea frequently flouts the maxim of quantity to emphasize her argument and persuasion, while Ben often flouts the maxim of relevance by redirect the conversation and giving unrelated comments. They both also flout the maxims of quality and manner to create humor, conceal true feelings. This study highlights how such linguistic strategies enhance the narrative, and it contributes to a deeper understanding of pragmatic phenomena in cinematic dialogue. Additionally, this research has differences from prior studies by applying the flouting maxim theory to romantic comedies with love-hate relationship dynamics.Keywords: Flouting Maxim, Romantic Comedy, Anyone but You